Sid the science kid. The ruler of thumb - Jim Henson Company; NCircle Entertainment ([Dallas, TX] : Distributed by NCircle Entertainment, 2010)
So many chores, so little time! If Sid doesn't fill his chore chart with stickers, he'll never get that new Turbo- Mega-Rocket Ship toy. What's so important about a chart anyway? Sid soon learns that charts are great science tools for comparing and contrasting things like snacks, pets, and even chores! When playing with a rolie polie bug, Sid discovers another amazing science tool, the magnifying glass.
The sticker chart -- The rolie polie -- Enough with the seashells -- The whale episode.
Title from container.
Originally broadcast on PBS Kids television as individual episodes in 2009.
Special features: Includes one compact disc that has 9 songs from the show.
DVD, NTSC, region 1, Dolby digital.
Keywords: Science -- Study and teaching -- Juvenile films; Charts, diagrams, etc. -- Juvenile films; Science -- Study and teaching -- Aids and devices -- Juvenile films; Magnifying glasses -- Juvenile films; Science -- Study and teaching -- Drama; Charts, diagrams, etc. -- Drama; Science -- Study and teaching -- Aids and devices -- Drama; Magnifying glasses -- Drama; Science television programs; Fantasy television programs; Children's television programs; Animated television programs; Television series